ANALISIS STRUKTUR STATIS PROVISION CRANE DENGAN SOFTWARE ANSYS 16.2 - Widyaningrum Febriolita; Jatisukamto Gaguk; Ilminnafik Nasrul (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2018)
Provision crane is one type of crane used for loading and unloading on ships. Material provision cranes used in this study are structural steel with a cross-section of hollow pipes. This study aims to analyze the strength and equilibrium of the structure of provision cranes. The research methodology used is the analysis of finite element analysis with Ansys 16.2 software. The results of the structural analysis show that the maximum deflection occurs at the end of the boom arm, namely aks max = 0.93843 mm; σymaks maximum yield stress = 36,233 MPa; the maximum yield strain εymaks = 0.027632%. Key Words: provision crane, finite element method, Ansys 16.2, δmaks, σy maks